The moderating role of industry clockspeed on the relation between supply chain integration practices and new product flexibility. Issue 3 (March 2023) - Sarfraz, Muddassar; Hussain, Ghulam; Nazir, Mian Sajid; Abdullah, Muhammad Ibrahim; Rashid, Muhammad Amir
Abstract: This study assessed the firm's new product flexibility in the recovery phase of COVID-19. Using the theoretical lens of organizational information processing theory, it established the relationship between supply chain integration practices (supply chain planning, internal integration, and supplier involvement) and new product flexibility. It also explained the moderating effect of industry clockspeed on supply chain integration practices and new product flexibility with the help of contingency theory. This study used an online survey method to collect data from plant managers, and we received 256 useable responses. We conducted a confirmatory factor analysis to test the validity and reliability of the scales, and we tested hypotheses using moderated multiple regression technique. The results showed significant positive relationships between supply chain integration practices and new product flexibility. The moderating effects hypotheses showed that industry clockspeed significantly and positively moderated on supply chain planning-new product flexibility and internal integration-new product flexibility links. But it negatively moderated on supplier involvement and new product flexibility. Our study departs from earlier studies in the field that were conducted under normal circumstances. We conducted our study in the recovery phase of COVID-19 in Pakistan, when firms, after fourteen days of complete lockdown, resumed their operations and experienced a new business landscape.